THE SCIENTIFIC CONCEPT OF PHYSICAL EDUCATION IMPROVEMENT IN HIGHER EDUCATIONAL INSTITUTIONS - Grigoryan, A. (Main Issues Of Pedagogy And Psychology, 2013)
Comparison of the various scientific concepts of the process organization of students physical education involves the introduction of modem approaches and methods for solving management problems. The aim of the work was to study modem features of improving the process of physical education in universities and developing a scientific concept of its organization. An analysis of the original experience of the systemic organization of the process of managing physical education in the higher educational institutions is carried out.